PENGARUH DOSIS DAN INTERVAL PUPUK DASAR TERHADAP PERTUMBUHAN TANAMAN NANAS (Ananas comosus [L.] Merr.) - Aulia, Fathia Nur; Rini, Maria Viva; Widyastuti, R.A. Diana; Karyanto, Agus (JURNAL AGROTROPIKA, 2025)
Pineapple (Ananas comosus [L.] Merr.) is one type of fruit that has an important role in Indonesia because it is a major export commodity, both in fresh and processed forms such as canned fruit and juice. Therefore, the development of pineapple production is a strategic matter. One of the steps taken to increase pineapple production is through proper and balanced fertilization. The objective of this study was to determine the best fertilizer package that supports the growth of pineapple plants. The research was conducted from November 2022 to March 2023 using a single-factor Randomized Group Design (RAK), consisting of treatments and repeated 4 times.  The treatment packages tested included the dose and interval of fertilization, namely: P0= 200 kg DAP + 200 kg Kiesirite + 300 kg K2SO4 + 50 kg ZA per ha (0, 30 HST), P1= 300 kg DAP + 300 kg Kiesirite + 300 kg K2SO4 + 50 kg ZA per ha (0, 30, 60 HST), P2= 300 kg DAP + 300 kg Kiesirite + 300 kg K2SO4+ 50 kg ZA per ha (0, 15, 45 HST), P3= 350 kg DAP + 350 kg Kiesirite + 350 kg K2SO4 + 50 kg ZA per ha (0, 30, 60 HST), and P4= 350 kg DAP + 350 kg Kiesirite + 350 kg K2SO4 + 100 kg ZA per ha (0, 15, 45 HST). In each experimental unit, 5 sample plants were selected, so that the total plants observed were 100 sample plants. The data were analyzed using analysis of variance, and the F test showed significant differences which were then further tested with the Least Significant Difference (BNT) test at the 5% level.  The results showed that in general, fertilizer doses and intervals had no significant effect on most of the observed variables, except on d-leaf width and d-leaf length.  The fertilizer package in the P0 treatment (200 kg DAP + 200 kg Kiesirite + 300 kg K2SO4 + 50 kg ZA) per ha proved to be the best to support pineapple plant growth. Keywords: dosage, fertilization frequency, pineapple, inorganic fertilizer